TRAUMA AND RESILIENCE IN MUSIC EDUCATION haunted melodies. - Bradley, Deborah; Hess, Juliet ([S.l.] : ROUTLEDGE, 2021)
Trauma and Resilience in Music Education: Haunted Melodies considers the effects of trauma on both teachers and students in the music class- room, exploring music as a means for working through traumatic expe- riences and the role music education plays in trauma studies. The volume acknowledges the ubiquity of trauma in our society and its long-term deleterious effects while showcasing the singular ways music can serve as a support for those who struggle. In twelve contributed essays, authors examine theoretical perspectives and personal and societal traumas, providing a foundation for thinking about their implications in music education. Topics covered include: Philosophical, psychological, sociological, empirical, and narrative perspectives of trauma and resilience. How trauma-informed education practices might provide guidelines for music educators in schools and other settings Interrogations of how music and music education may be a source of trauma Distinguishing itself from other subjects--even the other arts--music may provide clues to the recovery of traumatic memory and act as a tool for releasing emotions and calming stresses. Trauma and Resilience in Music Education witnesses music's unique abilities to reach people of all ages and empower them to process traumatic experiences, providing a vital resource for music educators and researchers.
Keywords: MUSIC / Instruction & Study / General; EDUCATION / Teaching Methods & Materials / Arts & Humanities; Music -- Instruction and study -- Psychological aspects; Music -- Instruction and study -- Social aspects; Psychic trauma -- Patients -- Rehabilitation; Psychic trauma -- Social aspects; Psychic trauma -- Treatment; Resilience (Personality trait); Music therapy